(3MGTjI eOGQc GdCMcGes - (3GdHgHgGfj, eMeO HGbQ GdhMjO, J (B1210(3g`s ((3egOjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3GYde Cf GdeYQha ef ePgH(B... (3Hd fbd LeY ef GdabgGA GdELeGYs
(3BNQgG (B:s
(3dCfg jbhd HGdEYGOI eGOGe aj GdhbJ aJchf TGPI aJYjf GdYed Ydi GdGSJMHGHs
(3JHUQI GdYfhGf (B:s
(3aj GdCYdGe(B: (3MGTjI Ydi eaGJjM GdCMcGe, haj gOjI GdYGQajf, hEjVGM Gdecfhf(B: (3GdaPGdc aj TQM GdeOGQcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajfs
(3CYjGf GdTjYI (B44: 135s
(3EjVGM Gdecfhf(B:s
Keywords: (3CUhd Gdabgs